A new ant genus from southern Argentina and southern Chile, Patagonomyrmex (Hymenoptera: Formicidae) - Johnson, Robert A.; Moreau, Corrie S. (Zootaxa, 2016)
The ant genus Pogonomyrmex (Hymenoptera: Formicidae: Myrmicinae) comprises 71 described species that occur in North America, South America, and Hispaniola, and it is the nominal genus in the recently established tribe Pogonomyrmecini. A molecular phylogeny using 3,647 base pairs from fragments of one mitochondrial gene (cytochrome oxidase I) and five nuclear genes (long-wavelength rhodopsin, elongation factor 1α F1, elongation factor 1α F2, wingless, rudimentary) inferred that Pogonomymrex was not monophyletic. The vast majority of species belonged to a monophyletic clade (Pogonomyrmex sensu stricto), whereas species in the Po. angustus-group formed a second lineage outside of Pogonomyrmex and Hylomyrma, the latter being the only other genus in the tribe. To maintain monophyly of Pogonomyrmex, we create the genus Patagonomyrmex gen. n., which consists of the three angustus-group species (Patagonomyrmex angustus comb. n., Patagonomyrmex laevigatus comb. n., and Patagonomyrmex odoratus comb. n.) that are sister to all other pogonomyrmecines. The genus is restricted to southern Argentina and southern and southcentral Chile. Workers are characterized by: (1) poorly-developed psammophore that consists of short to medium-length hairs scattered over the ventral surface of the head, (2) anterior clypeal margin strongly convex in full-face view, (3) clypeus strongly convex in profile, (4) superior and inferior propodeal spines long, (5) dorsal surface of promesonotum smooth and shiny, lacking rugae or if rugae present, then interrugae strongly granulate-punctate, (6) anteroventral margin of peduncle of the petiole with a small, acuminate spine, and (7) palp formula 5,4. We also provide information on biology, distribution maps, and a key to workers, queens, and males in English and Spanish.